Rezension von „Europarl“ - Claes Neuefeind (RIDE, 2018)
The Europarl corpus, short for „European Parliament Proceedings Parallel Corpus 1996-2011“, is provided by the School of Informatics, University of Edinburgh. Europarl was first published in 2001, the latest release (May 15th, 2012) includes the parliament proceedings from 1996-2011. There is no dedicated user interface, since Europarl is primarily meant to support research on machine translation, which has to rely on parallel texts. Beyond that, it is well suited for other NLP research involving multilingual issues. The resource is freely downloadable. Being one of the standard resources in the field of statistical machine translation, it comes as a source release with accompaining tools that were used for compiling the resource. The simple annotation and formatting makes the source files easy to use in different contexts of application.